LNMR Study on Microstructure Characteristics and Pore Size Distribution of High-Rank Coals with Different Bedding. (7th October 2021) - Liu, Jiajia; Hu, Jianmin; Shen, Mengqi; Yang, Ming; Fang, Yingxiang
Abstract : In order to study the pore structure characteristics of high-rank coals with different bedding, NMR experiments were carried out for high-rank coals with different bedding angles (0°, 30°, 45°, 60°, and 90°). The results show that the distribution of T 2 map of high-rank coal with different bedding is similar to some extent, showing a double peak or triple peak distribution, and the first peak accounts for more than 97% of the total, indicating that small holes are developed in high-rank coal with different bedding, while macropores are not developed. The influence of bedding angle on the fracture proportion is less than 0.3%. Compared with the fracture proportion, the effect of bedding angle on the proportion of microhole, medium hole, and large hole is greater and presents a certain rule. There are certain differences in T 2 cutoff value ( T 2C ) of high-rank coal with different bedding. The relationship between bedding angle and T 2C conforms to exponential function, and the correlation degree R 2 is 0.839. The research results provide a theoretical basis for gas extraction and utilization and prevention of gas disaster in coal mines in China.